Potential mechanisms underlying the cardiovascular benefits of sodium glucose cotransporter 2 inhibitors: a systematic review of data from preclinical studies. Issue 2 (26th November 2018) - Chin, Ken Lee; Ofori-Asenso, Richard; Hopper, Ingrid; von Lueder, Thomas G; Reid, Christopher M; Zoungas, Sophia; Wang, Bing H; Liew, Danny
Abstract: There is growing evidence from Phase III randomized clinical trials of the cardiovascular benefits of sodium glucose cotransporter 2 (SGLT2) inhibitors in patients with diabetes mellitus. It is hypothesized that these benefits are mediated by mechanisms other than glucose control. To address this, we performed a systematic review of data from preclinical studies examining the direct cardioprotective effects of SGLT2 inhibitors. Medline, EMBASE, CINAHL, and International Pharmaceutical Abstracts databases were searched for preclinical studies that examined the potential cardioprotective effects of SGLT2 inhibitors. Submission documents to the US Food and Drug Administration, European Medicines Agency, and Japanese Pharmaceutical and Medical Devices Agency for the registration of SGLT2 inhibitors were also reviewed. A total of 36 reports were included in the final analysis. The potential direct cardiovascular benefits of SGLT2 inhibitors include: augmentation of signal transducer and activator of transcription 3; inhibition of sodium hydrogen exchange; reduction of atherosclerosis; modulation of natriuretic peptides; vasodilation; modulation of sympathetic tone; and reduction of inflammation, oxidative stress, endoplasmic reticulum stress, and cardiac glucose uptake via down-regulation of SGLT1 expression. There are a number of mechanisms by which SGLT2 inhibitors may exert cardiovascular benefits beyond glycaemic control.